KONSEP NIKAH MUT’AH DALAM PERSPEKTIF PENDEKATAN MA’NA-CUM-MAGHZA (At-Tibyan, 2025)
Mut'ah marriage (contract marriage), which went viral a few years ago in Indonesia, is still often practiced today. Mut'ah marriage is a marriage that is limited to a certain time as agreed by both parties. This marriage is usually carried out by foreigners and local residents who are on vacation or business, while the woman comes from the village area. Mut'ah marriages have a negative impact on women and the children they give birth to because the man can simply leave after the contract period has expired. Therefore, this research aims to find out how the concept of mut'ah marriage and what the impact of the marriage is, then look at the interpretation of QS. An-Nisa' verse 24 relating to mut'ah marriage with the ma'nā-cum-maghzā approach. This research is a library research with a descriptive-analytical qualitative method. In this research, the method of data collection method used is documentation. Documentation data that collected in the form of text verses of the Qur'an, books, books, journals, articles and others. The data analysis technique used in this research is taken from the data analysis technique used in this research is taken from the ma'nā-cum-maghzā approach, namely by means of linguistic analysis, intratextuality, intertextuality, historical analysis both micro and macro, and historical and dynamic phenomenal significance. The results of this study conclude that mut'ah marriage occurs in Indonesia, especially in several tourist areas. The factors behind the practice of this marriage are difficult financial conditions, lack of employment opportunities and low education. In interpreting QS. An-Nisa' verse 24, the mufassirs from classical to contemporary agree that mut'ah marriage is prohibited. Then the results of the ma'nā-cum-maghzā approach found historical phenomenal significance, namely the command not to marry married women unless they have separated from their husbands and this verse also conveys the message that Allah SWT. commands a man to give a dowry if he wants to marry a woman.